2016
DOI: 10.1212/wnl.0000000000003359
|View full text |Cite
|
Sign up to set email alerts
|

Safety of intrathecal autologous adipose-derived mesenchymal stromal cells in patients with ALS

Abstract: Objective: To determine the safety of intrathecal autologous adipose-derived mesenchymal stromal cell treatment for amyotrophic lateral sclerosis (ALS).Methods: Participants with ALS were enrolled and treated in this phase I dose-escalation safety trial, ranging from 1 3 10 7 (single dose) to 1 3 10 8 cells (2 monthly doses). After intrathecal treatments, participants underwent standardized follow-up, which included clinical examinations, revised ALS Functional Rating Scale (ALSFRS-R) questionnaire, blood and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
81
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(88 citation statements)
references
References 7 publications
5
81
0
2
Order By: Relevance
“…Almost all organ system have been implicated in adipose‐derived cell therapy. The indication for treatment in the included studies was (in order count) soft tissue , gastrointestinal , musculoskeletal , rheumatological , ulcer/ischemic limb , urogenital , cardiac , neurological , immunological , pulmonary , and ophthalmological (Fig. A).…”
Section: Resultsmentioning
confidence: 99%
“…Almost all organ system have been implicated in adipose‐derived cell therapy. The indication for treatment in the included studies was (in order count) soft tissue , gastrointestinal , musculoskeletal , rheumatological , ulcer/ischemic limb , urogenital , cardiac , neurological , immunological , pulmonary , and ophthalmological (Fig. A).…”
Section: Resultsmentioning
confidence: 99%
“…We compared three injections of cells or their CondM applied at intervals of 14 days into SC, or cells injected into M, or a combination of both applications—SC + M. We used lumbar puncture as a route of delivery. This is the most common way of how ALS patients are treated with different types of stem cells . In our previous study, we reported a prolonged lifespan and an improved neurological outcome in the SOD1 rats treated with hMSC in one single injection into cisterna magna at the onset of the disease.…”
Section: Discussionmentioning
confidence: 96%
“…The most recent clinical investigations, in patients with ALS who underwent hMSC transplantation, have shown procedural safety and clinical proof of principle with modest neurological benefits. The most frequently used route of delivery in patients is via lumbar puncture, either in single dose or repeatedly .…”
Section: Introductionmentioning
confidence: 99%
“…With the advancement of stem cell research, diverse types of stem cell therapy have been conducted; however, randomized controlled trials on cell-based therapies for ALS were not published until early 2016. To date, most clinical trials of MSCs for ALS were single-arm phase 1 22,23 or phase 2 24 trials focusing on the safety, feasibility, and possible efficacy, whereas only a few compared natural historical data. 25,26 In this study, 2 repeated treatments with intrathecal autologous BM-MSCs (1 × 10 6 cells per kg with a 26-day interval) showed significant therapeutic benefit with safety in patients with ALS.…”
Section: Discussionmentioning
confidence: 99%